Trypanosoma brucei: posttranscriptional control of the variable surface glycoprotein gene expression site. - Pays, E (1989)
The arrest of variable surface glycoprotein (VSG) synthesis is one of the first events accompanying the differentiation of Trypanosoma brucei bloodstream forms into procyclic forms, which are characteristic of the insect vector. This is because of a very fast inhibition of VSG gene transcription which occurs as soon as the temperature is lowered. We report that this effect is probably not controlled at the level of transcription initiation, since the beginning of the VSG gene expression site, about 45 kilobases upstream from the antigen gene, remains transcribed in procyclic forms. The permanent activity of the promoter readily accounts for the systematic reappearance, upon return to the bloodstream form after cyclical transmission, of the antigen type present before passage to the tsetse fly. The abortive transcription of the VSG gene expression site appears linked to RNA processing abnormalities. Such posttranscriptional controls may allow the modulation of gene expression in a genome organized in large multigenic transcription units.